2022
DOI: 10.3390/vaccines10050765
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Predictors of COVID-19 Vaccination Acceptance among Greek Health Care Workers and Administrative Officers of Primary Health Care Centers: A Nationwide Study Indicating Aspects for a Role Model

Abstract: Background: Τhe study aims to identify factors associated with COVID-19 vaccine acceptance and to investigate knowledge and perceptions of Primary Health Care Centers (PHCC) personnel, who acted as pioneers in the national COVID-19 vaccination strategy. Methods and Materials: A nationwide cross-sectional survey was conducted by distributing an online anonymous questionnaire comprising 25 questions during the first semester of 2021. Results: Approximately 85.3% of the 1136 respondents (response rate 28.4%) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 41 publications
2
6
0
Order By: Relevance
“…Conversely, nurses are one of the most vaccine-resistant occupational groups. Similar findings were observed in studies related to COVID-19 vaccination [ 28 , 29 , 50 , 51 ]. This behavior demonstrates a lack of risk perception ability for this specific occupational group, which could suggest hazards for both themselves and their patients.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Conversely, nurses are one of the most vaccine-resistant occupational groups. Similar findings were observed in studies related to COVID-19 vaccination [ 28 , 29 , 50 , 51 ]. This behavior demonstrates a lack of risk perception ability for this specific occupational group, which could suggest hazards for both themselves and their patients.…”
Section: Discussionsupporting
confidence: 90%
“…This confirms the results of other surveys demonstrating greater hesitancy of nurses toward SIV vaccination compared with physicians [ 17 , 42 , 43 ]. Moreover, several studies noted that physicians are more vaccine-acceptant, whether related to SIV or any other vaccine [ 28 , 29 , 39 , 44 , 45 , 46 , 47 , 48 ]. Similarly, a Greek survey conducted during the H1N1 pandemic examining HCWs’ uptake of the H1N1 vaccine revealed that physicians were more acceptant compared to other HCWs [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to our findings, the rate of resident doctors who adhered to the COVID-19 vaccination programme is close to 100%; in fact, only 0.26% of them did not receive a vaccination. These results show a very high compliance rate of MRs towards compulsory vaccination even compared to studies performed in other states [ 27 , 28 , 29 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 48%